The Relationship Between Cash Flow Shocks, Fixed Assets, and External Financing in Emerging Market (The International Research Journal of Management Science, 2025)
Purpose: This study examines how cash flow shocks and the interaction between cash flow and fixed assets influence external financing decisions of financially constrained and unconstrained firms in Nepal.Design/Methodology: The analysis is based on secondary data from annual reports and the Nepal Stock Exchange (NSE), covering 19 non-financial listed firms over the period 2004–2022. The study is quantitative in nature and adopts descriptive and causal-comparative research design.Findings: The results indicate that financially strong firms reduce their reliance on external financing as cash flows improve, while financially constrained firms show limited responsiveness to cash flow variations. However, during periods of credit market instability, constrained firms experience greater uncertainty but demonstrate a stronger inclination to seek external financing for growth opportunities. The study also reveals a positive interaction between cash flow and fixed assets, underscoring the role of asset tangibility in financing strategies under financial constraints.Implications/Limitations: The findings offer practical implications for policymakers and financial institutions in framing credit policies tailored to firm-level constraints and asset structures. The study is limited to listed non-financial firms, which may restrict wider generalizability.